The role of socio-demographic characteristics in mediating relationships between people and nature - Kim C. Zoeller (Resilience Alliance, 2021)
Research on ecosystem services has focused primarily on questions of availability or supply and often assumes a single human community of identical beneficiaries. However, how people perceive and experience ecosystem services can differ by socio-demographic characteristics such as material wealth, gender, education, and age. Equitable environmental management depends on understanding and accommodating different perceptions of ecosystem services and benefits. We explored how socio-demographic characteristics influence people's perceptions of birds. We identified morphological and behavioral traits of birds that people care about and used these to group bird species into "cultural functional groups." Cultural functional groups of birds are defined by shared characteristics that local people perceive as contributing to cultural ecosystem services or disservices (in the same way that foraging guilds for birds can be defined by dietary information). Using perception data for 491 bird species from 401 respondents along urban-rural gradients in South Africa, we found that socio-demographic characteristics were strongly associated with human preferences for different avian cultural functional groups. Our results provide a strong quantitative demonstration that the provision of cultural ecosystem services and benefits depends on the recipient of the service and not just on the ecological community that is present.